EKSTRAKSI PEKTIN POD HUSK KAKAO SECARA BASAH MENGGUNAKAN LARUTAN NATRIUM HIDROKSIDA PADA BERBAGAI KONSENTRASI - Munir, Muh. Misbahul; Rahim, Abdul; Rahmatu, Rostiati (AGROTEKBIS, 2018)
The aim of this research is to find out the optimum concentration of Pod Husk Cacao extraction by wet method using different Sodium Hydroxides (NaOH) concentrations. The researsh used Simple Complete Random Design with one factor which consists of five levels of treatment : 0.5 M ; 1 M ; 1.5 M ; 2.0 M and 2.5 M, the treatments were replicated 4 times so there were 20 experimental units. If the treatment has significant effect then it tested using Tukeyâs Honestly Significant Different level 5% or 1%. The results showed that the most optimum extraction was obtained using NaOH 1.59 M, which the number of rendement was 11,15%,Â methoxil content was 50.22 %, galacturonat content was 46.62%, and pectin purity was 9.19%. Pectin of pod husk cocoa could be extracted using NaOH concentration between 1 â 2 M with wet method.Â Key Words:, Concentration of Natrium hydroxides, Pectin, Pod husk cacao, Wet method